Analisis Pengaruh Cap Tip (Electrode Tips) terhadap Sisa Spatter Spot Area Body Shop PT. Isuzu Motor Indonesia Plant Karawang - Rianita Puspa Sari; Dene Herwanto; Ana Suryana (Universitas Bunda Mulia, 2017)
Body Shop consists of the assembly production process area of sub items or components combined with car cabin manufactured mostly using the base material of metal plate by using electric welding resistance method or Spot Welding. Spot Welding can be done by using an electrode with another name CAP TIP (Electrode Tips), made of copper alloy run by a large electric current, in a relatively short time. The grafting material process generates spatter. The spatter spots are discovered on the cabin plane. This study aims to analyze the effect of CAP TIP (electrode tips) on the remaining spatter spot found on car cabin using ANOVA method. The survey data were obtained from 3 types of CAP TIP (PG 1712, PG 1431, PG 1777-50) of 10 types of CAP TIP used in the body shop area along with the amount of residual spatter produced. The results revealed variant similarity of the three types compared from the Levene statistic value of 1,563, with the average number of residual spatter most produced by CAP TIP PG 1712 as 47.17, while the F value of 0.914 with the significance of 0.443 indicating no significant CAP TIP type difference against the rest of the spatter, thus H0 is rejected. This proves that there is no effect of CAP TIP (electrode tips) on the remaining spatter spots.Keywords: Electrode tips, Welding spot, Spatter spot, ANOVA